THE EFFECT OF SALARY, CAREER DEVELOPMENT AND REWARDS ON JOB SATISFACTION (STUDY OF HUMAN RESOURCE MANAGEMENT LITERATURE) - Ricardo, Ricardo (Dinasti International Journal of Digital Business Management, 2022)
The Literature Review article on the Effect of Salary, Career Development and Rewards on Job Satisfaction is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Human Resource Management. The method of writing this Literture Review article is using the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this study are: 1) Salary has an effect on Job Satisfaction; 2) Career Development has an effect on Job Satisfaction; and 3) Awards have an effect on Job Satisfaction. Apart from these 3 exogenous variables that affect the endogenous variable Job Satisfaction, there are still many other factors including Work Environment, Organizational Culture and Workload variables.